Analisis Sistem Pengelolaan Surat Masuk Dan Surat Keluar Terhadap Tata Kelola Perizinan Perdagangan Luar Negeri Pada Dinas Perindustrian Dan Perdagangan Kota Medan - Ariyadi Ariyadi; Aumalia Hanipah; Emi Yani Teta Br Tarigan; Marliyah Marliyah (Jurnal Manajemen Riset Inovasi, 2024)
The management of incoming letters and outgoing letters at the Department of Industry and Trade of Medan City refers to the processes and activities carried out to receive, process, and distribute letters received or sent by Disperindag. In this study, it will be discussed how the incoming and outgoing mail management system on Disperindag's foreign trade licensing governance, as well as the obstacles experienced in the process of Disperindag's incoming and outgoing mail governance. this type of research is qualitative research that uses a series of sentences to describe the data. The method used in this research is descriptive method. Descriptive method is a method whose data sources are in the form of text, images and in the form of sources from books. and information from employees and the head of the Medan Industry and Trade Office. This research uses written data sourced from interviews during college internships, scientific journal books and previous research. The results of this study indicate that the process of handling incoming letters includes receiving letters, recording letters, sending letters, and processing letters. While the processing of outgoing letters includes preparing letters, typing letters, signing letters, recording letters, copying letters, and sending letters.